Penerapan Model Pembelajaran Think Pair Share untuk Meningkatkan Pemahaman Konsep Matematis Peserta Didik Kelas VIII SMPN 1 Padang Panjang (Departemen Matematika, 2019)
Understanding the concept of mathematics is one important thing that must be possessed learners. Based on the observations that have been done, it appears that the understanding of mathematical concepts of learne sclass VIII SMPN 1 Padang Panjang still low. One effort that can be done is to apply the Think Pair Share Learning Model. This research type is combination of quasi experiment and descriptive. The purpose of this research is to describe whether understanding mathematical concepts of learners who learn by Think Pair Share learning is better than learners who learn by direct learning. The instrument used was test of understanding mathematical concepts of learners. Based on the results showed that understandingof mathematical concepts of learnerswho learn by Think Pair Share Learning Model is better than understanding of the concept of learners who learn by using the Direct Learning Model. Keywords –Understanding Of Mathematical Concepts, Think Pair Share Learning model, Direct Learning model